Life in the Time of a Pandemic Social, Economic, Health and Environmental Impacts of COVID-19-Systems Approach Study - Sahin, Oz; Richards, Russell (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
It has been confirmed that the number of cases and the death toll of COVID-19 are continuing to rise in many countries around the globe. Governments around the world have been struggling with containing and reducing the socioeconomic impacts of COVID-19; however, their respective responses have not been consistent. Aggressive measures imposed by some governments have resulted in a complete lockdown that has disrupted all facets of life and poses massive health, social, and financial impacts. Other countries, however, are taking a more wait-and-see approach in an attempt to maintain business as usual. Collectively, these challenges reflect a super wicked problem that places immense pressure on economies and societies and requires the strategic management of health systems to avoid overwhelming them-this has been linked to the public mantra of 'flattening the curve', which acknowledges that while the pandemic cannot be stopped, its impact can be regulated so that the number of cases at any given time is not beyond the capacity of the health system. Dynamic simulation modelling is a framework that facilitates the understanding/exploring of complex problems, of searching for and finding the best option(s) from all practical solutions where time dynamics are essential. The papers in this book provide research insights into this super wicked problem and case studies exploring the interactions between social, economic, environmental, and health factors through the use of a systems approach.